Sleep Disturbances in Neurological Disease: A Target for Intervention - Khambadkone, Seva G.; Benjamin, Sara E. (Seminars in Neurology, 2022)
Sleep is a biological function required for neurological and general health, but a significant and under-recognized proportion of the population has disturbed sleep. Here, we briefly overview the biology of sleep, sleep requirements over the lifespan, and common sleep disorders. We then turn our attention to five neurological diseases that significantly contribute to global disease burden and neurology practice makeup: epilepsy, headache, ischemic stroke, Parkinson's disease, and Alzheimer's disease. For each disease, we review evidence that sleep disturbances contribute to disease risk and severity and discuss existing data that addressing sleep disturbances may have disease-modifying effects. We provide recommendations derived from the literature and existing clinical guidelines to facilitate the evaluation and management of sleep disturbances within the context of each neurological disease. Finally, we synthesize identified needs and commonalities into future directions for the field and practical sleep-related recommendations for physicians caring for patients at risk for or currently suffering from neurological disease.
Keywords: sleep; sleep apnea; insomnia; epilepsy; headache; stroke; Parkinson's disease; Alzheimer's disease